Rapporter - Mariager Anderson, Kristina; Chami, Anders; Teich Geertinger, Axel; Jørgensgaard Graakjær, Nicolai; Holme Hansen, Thomas; Steinskog, Erik; Jensen, Eva Maria (Danish Yearbook of Musicology, 2006)
Research Projects Music teacher education in Denmark (Kristina Mariager Anderson & Anders Chami) Sinfonia und Concerto um 1700 (Axel Teich Geertinger) Music in the television commercial (Nicolai Jørgensgaard Graakjær) Knud Jeppesen – renowned musicologist and overlooked composer (Thomas Holme Hansen) Conferences The Local, the Regional and the Global, Copenhagen 2005 (Erik Steinskog) Nordic Music Editions Symposium, Kopenhagen 2005 (Axel Teich Geertinger) Lutoslawski-symposium i København, november 2005 (Eva Maria Jensen) Danish Musicological Society, 2005 (Thomas Holme Hansen)